Peran Public Speaking Reporter Dalam Pembuatan Konten Vidio Reportase English For Broadcasting - Sukma, Stevi Nanda; Eriend, Dion (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This final assignment aims to describe and understand the importance of the role of public speaking reporters in creating English reportage video content for broadcasting as well as their ability to speak English, especially in the field of broadcasting. Public speaking is related and closely related to a reporter. Public speaking is the art of speaking and processing words in front of a large audience. Public speaking comes from two words, namely "public" which means general, public, society and "talk" which means to talk. A reporter must have the ability to do public speaking because one of his activities is conveying messages and information to the public so that the choice of language and processing of words must be paid attention to so that the content of the message can be conveyed and understood. The theory used in this final assignment is Aristotle's Rhetoric Theory. In his book "Rhetoric" Aristotle put forward the meaning of rhetoric, namely the ability to choose and use language in certain situations effectively to persuade other people. This theory is related to the final task of making a video reportage because in this video, a reporter must have the ability to do public speaking because one of the information activities is conveying messages to the public so the choice of language and processing of words must be conveyed effectively. The results of this final assignment report discuss how important the role of public speaking reporters is in creating English reportage video content for broadcasting as well as their ability to speak English, especially in the field of broadcasting. Especially in the world of journalism and broadcasting, if you use English it will reach and cover a wide area and have various other benefits. Therefore, we must continue to hone our skills in public speaking and English because this is one of the assets for getting great opportunities and opportunities in various fields of life.